Impact of ownership structure, underwriter reputation and IPO proceed size to the level of IPO underpricing - Darmawan, D; Bustaman, Yosman (Diponegoro International Journal of Business, 2024)
The research aims to examine and confirm whether the underpricing phenomena exist in the Indonesia IPOs during the observation period Year 2017 to 2021 and explain its variations. This research investigate the effect of key determinants factors that have influenced the level of IPO underpricing. The research used the secondary data analysis with cross sectional studies of the observation data of 254 IPO companies. The analysis were applied with several trading period time frame i.e. 1 day, 1 month, 3 month and 6 month. The result shows that the underpricing phenomenon is confirmed in Indonesia’s IPO with number of companies that experience underpricing has reached 85% on the first of trading day. Underwriter reputation is positively related to the level of underpricing in the first trading day period. Companies with larger size of IPOs are underpriced less than the smaller ones. Meanwhile the ownership retention is negatively related with the level of underpricing. The ownership identity and ownership type are not associated to the level of underpricing. In addition, the research find that these variables are not associated to the level of underpricing for period other than 1 trading day.